Critical analysis of the Brazilian Charter of Integrated Prevention in the Field of Health in the Perspective of Physical Education through the radical focus of health promotion - Carvalho, Fabio F. B. de (Saúde e Sociedade, 2009)
This work intends to provide a contribution so that the professional area and the field of knowledge referring to Physical Education view health in a broader way, overcoming the biological focus which usually occurs. It has a qualitative character and was based on research into bibliographic sources in order to develop a monograph upon the completion of the Public Health specialization course at the National School of Public Health Sergio Arouca, of the Oswaldo Cruz Foundation. The Brazilian Charter of Integrated Prevention in the Field of Health in the Perspective of Physical Education, a document written by the Federal Council of Physical Education (CONFEF) in 2006, was critically analyzed based on the radical focus of Health Promotion. This focus can be summarized as an articulation between health and life conditions, emphasizing social equity interrelations, through the increase in the capacity for popular participation, intersectoriality, promotion of healthy public policies, creation of environments that are favorable to health, and through a reorientation of the health system, based on a broader view of the health-disease process and on the recognition of the multi-determination of this process (OMS, 1986; Buss, 2000, 2001, 2007; Pedrosa, 2004). We concluded that the document that we analyzed assumes a biological and medical view concerning the relation between Physical Education and society. We recommend that this document is revised based on the critical perspective connected with the Physical Education field, which relates physical activities and health to broader social issues which prevent subjects from making healthier decisions, such as economic, cultural, ethnic and political conditioning factors.